The comparison of an effectiveness mangkokan leaf extract (notophanax) and chloramphenicol to salmonella typhi and pseudomonas bacteria - Sri Wahyuni Nasution; Anita Rosari; Adiansyah Batubara (Jurnal Info Sains : Informatika dan Sains, 2024)
Salmonella Typhi and Pseudomonas bacteria are two pathogenic microorganisms that have the potential to cause serious disease in humans. Salmonella Typhi is the main cause of typhoid fever, while Pseudomonas is a group of bacteria that can cause infections, especially in individuals with weak immune systems. Mangkokan leaves (Nothopanax scutellarin Merr.) and Chloramphenicol are thought to be effective as antibacterials for these two bacteria. This study aimed to compare the effectiveness of Bangkok leaf extract (Nothopanax scutellarin Merr.) and chloramphenicol against Salmonella Typhi and Pseudomonas bacteria. The type of research used was a laboratory experiment at the Microbiology Laboratory, Faculty of Medicine, University of North Sumatra (FK USU) Medan. The test used 250 grams of Bangkok (Nothopanax scutellarin Merr.) leaf extract which was macerated using 70% ethanol to obtain a thick ethanol extract while Chloramphenicol had a concentration of 100 ppm. The test results were compared with the inhibition zone diameter parameters of the Clinical and Laboratory Standards Institute (CLSI, 2013). Based on laboratory test results, show that Bangkok leaf extract (Nothopanax scutellarium Merr.) with a consistency of 70% ethanol is resistant to Salmonella Typhi bacteria (x̄ =9.17±0.029)and Pseudomonas (x̄ =8.03±0.058)while Chloramphenicol is sensitive to Salmonella Typhi (27.0 mm) and Pseudomonas (27.0 mm) bacteria.